Traditional and modern medicine working in tandem - E. Pretorius (AOSIS, 1991)
Because of the many problem relating to health care delivery in Africa, it is becoming apparent that neither the exclusive/monopolistic nor the tolerant legislative systems should be tolerated any longer. Especially since the Alma Ata Conference held by the WHO/UNICEF there has been growing impetus towards either inclusive/parallel (the beneficial co-existence of traditional and modern medical systems), or integrated systems. Although the idea of making traditional and modern medicine work in tandem in a united treatment context has its merits, it is also plagued by issues such as the nature of the products of an integrated training, resistance by stubborn protagonists of either of the two systems, or that only lip-service is paid to the idea of co-operation. Nevertheless, it is believed that all interest groups - the authorities responsible for health care delivery, the Western-trained health care workers, the traditional healers and the users of these services - stand to gain from such liaison.